Chapter 4 The Scholar-Practitioner of Yoga in the Western Academy - Singleton, Mark (Taylor & Francis, 2020)
The Routledge Handbook of Yoga and Meditation Studies is a comprehensive and interdisciplinary resource, which frames and contextualises the rapidly expanding fields that explore yoga and meditative techniques. The book analyses yoga and meditation studies in a variety of religious, historical and geographical settings. The chapters, authored by an international set of experts, are laid out across five sections.